Apelin is a marker of the progression of liver fibrosis and portal hypertension in patients with biliary atresia - Chen, Wei; Oue, Takaharu; Ueno, Takehisa; Uehara, Shuichiro; Usui, Noriaki; Fukuzawa, Masahiro (Pediatric surgery international, 2013)
Purpose Apelin, the endogenous ligand of the angiotensin-like-receptor 1 (APJ), is thought to play an important role in liver disease. This study investigated the apelin expression in different stages of biliary atresia (BA) and investigated whether it is associated with the progression of disease. Methods Liver tissues were obtained from patients at Kasai’s procedure (KP), the follow-up stage after KP (Post-KP) and at liver transplantation (LT). Immunohistochemistry for apelin and its receptor APJ and real-time quantitative reverse transcriptase polymerase chain reaction for apelin mRNA expression were conducted. Results The immunohistochemical study revealed that apelin was mainly localized in the perivenular areas of control liver tissue, and slightly detected in the hepatic stellate cells (HSC) and hepatocytes, whereas intense apelin immunoreactivity was detected in perivenular areas, HSC and hepatocytes of LT liver tissue. The apelin mRNA expression level was significantly higher in the LT group than in the KP and Post-KP group. Significant linear correlations were observed between the apelin mRNA level and liver fibrosis, serum total bilirubin and the grade of esophageal varices. Conclusions The hepatic apelin–APJ system is markedly activated in the progression of BA, especially in end-stage cirrhosis. The apelin expression level accurately reflects the severity of hepatic fibrosis and esophageal varices and therefore could be used as a prognostic factor in BA patients.